Contrasting motivational orientation and evaluative coding accounts: on the need to differentiate the effectors of approach/avoidance responses - Kozlik, Julia; Neumann, Roland; Lozo, Ljubica (Frontiers in Psychology, 2015)
Several emotion theorists suggest that valenced stimuli automatically trigger motivational orientations and thereby facilitate corresponding behavior. Positive stimuli were thought to activate approach motivational circuits which in turn primed approach-related behavioral tendencies whereas negative stimuli were supposed to activate avoidance motivational circuits so that avoidance-related behavioral tendencies were primed (motivational orientation account). However, recent research suggests that typically observed affective stimulus–response compatibility phenomena might be entirely explained in terms of theories accounting for mechanisms of general action control instead of assuming motivational orientations to mediate the effects (evaluative coding account). In what follows, we explore to what extent this notion is applicable. We present literature suggesting that evaluative coding mechanisms indeed influence a wide variety of affective stimulus–response compatibility phenomena. However, the evaluative coding account does not seem to be sufficient to explain affective S–R compatibility effects. Instead, several studies provide clear evidence in favor of the motivational orientation account that seems to operate independently of evaluative coding mechanisms. Implications for theoretical developments and future research designs are discussed.